Peraturan Pemerintah No 23 Tahun 2018 di Desa Klambir Lima Kebun Kecamatan Hamparan Perak - Destari Nurlaila Damanik; Teuku Radhifan Syauqi; Adik Irma (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the implementation of Government Regulation Number 23 of 2018 in Klambir Lima Kebun Village, Hamparan Perak District, which focuses on its impact on Micro, Small, and Medium Enterprises (MSMEs). PP Number 23 of 2018 regulates the reduction of the Final Income Tax (PPh) rate for MSMEs from 1% to 0.5% for taxpayers with a turnover of less than IDR 4.8 billion per year. This policy aims to ease the tax burden, simplify calculations, and improve MSME taxpayer compliance, while encouraging the growth of new entrepreneurs. This study uses a qualitative descriptive method with data collected through interviews, observations, and document analysis from MSME actors and village officials. The results of the study indicate that this tax rate reduction policy provides significant benefits for MSME actors in Klambir Lima Kebun Village. Business actors feel helped by the lower tax rate, so they can allocate more resources for business development. However, the level of taxpayer understanding of this regulation still varies. Most MSME actors do not fully understand the procedures for reporting and paying taxes in accordance with this policy, so they need further guidance and socialization from the government. This study concludes that the success of implementing PP Number 23 of 2018 at the village level is highly dependent on educational and mentoring efforts for MSME actors. This finding provides insight for the government in designing tax policies that are more inclusive and responsive to the needs of MSMEs.